1999
DOI: 10.1002/(sici)1097-0185(19990601)255:2<202::aid-ar10>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-related hypermineralization in the female proximal human femur

Abstract: Hip fracture incidence increases exponentially with age in virtually every human population that has been studied. In spite of this, relatively few studies have examined age-related changes in the metaphyseal cortex of the proximal femur. The present study investigates cortical aging changes in the female proximal femur, with particular reference to regions of hypermineralization. Thirty-three femora from Caucasian females were obtained at autopsy and analyzed using backscattered electron imaging. Variations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 37 publications
3
49
5
Order By: Relevance
“…These results are consistent with findings reporting increased mineralized tissue, areas of higher mineral content than the adjacent cortex, at the FN in elderly populations [4,5,37]. The origin of these highly mineralized areas may be due to subperiosteal calcification derived from the periosteum [11], necrotic tissue where minerals continue to accumulate [5] or calcified fibrocartilagenous tissue at points of attachments of tendons or capsules [5,37]. The presence of fully mineralized tissue areas may have implications for fracture strength and it has been reported that these highly mineralized regions make the formation and expansion of cracks easier [10].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with findings reporting increased mineralized tissue, areas of higher mineral content than the adjacent cortex, at the FN in elderly populations [4,5,37]. The origin of these highly mineralized areas may be due to subperiosteal calcification derived from the periosteum [11], necrotic tissue where minerals continue to accumulate [5] or calcified fibrocartilagenous tissue at points of attachments of tendons or capsules [5,37]. The presence of fully mineralized tissue areas may have implications for fracture strength and it has been reported that these highly mineralized regions make the formation and expansion of cracks easier [10].…”
Section: Discussionsupporting
confidence: 92%
“…The higher value of cBMD at the FN in the elderly women, compared to the TR (which decreased with age), may be due to the presence of highly mineralized areas in the FN cortex of elderly women. These results are consistent with findings reporting increased mineralized tissue, areas of higher mineral content than the adjacent cortex, at the FN in elderly populations [4,5,37]. The origin of these highly mineralized areas may be due to subperiosteal calcification derived from the periosteum [11], necrotic tissue where minerals continue to accumulate [5] or calcified fibrocartilagenous tissue at points of attachments of tendons or capsules [5,37].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have documented that both periosteal calcification and calcified fibrocartilage undergo osteonal remodeling. 134,140 Although this study did not document any calcified fibrocartilage, the abundant periosteal mineralized tissue did contain individual osteons, clearly separated from the periosteal bone surface, in some regions. Such mechanism could be an alternative explanation for femoral neck periosteal expansion with age.…”
Section: Microscopic Featuresmentioning
confidence: 54%
“…This leads to thinning of the cortex and trabecularization of the inner cortical layer [10]. On the other hand, hypermineralization of the bone and increase of true bone mineral density noted in aged patients [11] can lead to higher ultrasound velocity in the outer layer, thus, can confound the diagnostic outcome based on the velocity alone. That is why the knowledge about changes in elastic properties and the effective thickness of the cortex are of equal diagnostic value for better assessment of different types of osteopenia and detecting osteoporosis development in long bones at earlier stages.…”
Section: Introductionmentioning
confidence: 99%